Improvements on the fundamental parameters of the open cluster Tombaugh 1 through Washington system photometry - Piatti, Andres Eduardo (2004)
We present CCD photometry in the Washington system C and T1 passbands down to T1 ∼ 18.5 mag in the field of Tombaugh 1, a little studied open cluster located in the third Galactic quadrant. We measured T1 magnitudes and C −T1 colours for a total of 1351 stars distributed throughout an area of 13. 6 × 13. 6. A cluster radius of 4. 3 ± 0. 3 was estimated from star counts in 100-pixel a side boxes distributed throughout the entire observed field. Based on the best fits of isochrones computed by the Geneva group for Z = 0.008 to the T1 vs. C − T1 colour–magnitude diagram, we derive a colour excess E(C − T1) = 0.55 ± 0.10, equivalent to E(B − V) = 0.30 ± 0.05, a distance of (2.2 ± 0.5) kpc from the Sun and an age of 1.3 +0.1 −0.2 Gyr. The latter value is in good agreement with that derived from the independent metallicity δT1 index defined in Geisler et al. (1997, AJ, 114, 1920). An independent metallicity estimation using the [MT1 , (C − T1)0] plane with the standard giant branches of Geisler & Sarajedini (1999, AJ, 117, 308) yields [Fe/H] = −0.30 ± 0.25 dex, a value which lends support to the one obtained from the isochrone fit. Tombaugh 1 is then found to be a relatively metal-poor intermediate-age open cluster.